Formation of different magnetic phases and high Curie temperature ferromagnetism in Fe57-implanted ZnO film - Ozturk, M.; Demirci, E.; Gurbuz, O.; Guner, S.; Valeev, V.; Vagizov, F.; Khaibullin, R. (Elsevier Science Bv, 2015)
We investigated magnetic properties of ZnO thin film implanted with Fe-57 ions to the fluence of 1.00 x 10(17) ions/cm(2). Both vibrating sample magnetometry and magneto-optical Kerr effect measurements revealed strong room temperature ferromagnetism with similar hysteresis loops. Temperature dependent measurements showed a very high Curie temperature around 850 K. Conversion electron Mossbauer spectroscopy experiments proved the existence of paramagnetic Fe+3 and Fe+2 ions and also the presence of substitutional Fe atoms in the hexagonal ZnO crystal resulting in intrinsic ferromagnetic order. (C) 2014 Elsevier B.V. All rights reserved.
International Conference on Nanoscale Magnetism (ICNM-2013) -- SEP 02-06, 2013 -- Istanbul, TURKEY
Keywords: Co-Doped Tio2; Rutile; Semiconductors